2012
DOI: 10.1177/1066896912445921
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pelvic Lymph Node Metastases in Prostatic Adenocarcinoma

Abstract: Pelvic lymph node dissection (PLND) is currently the most accurate staging modality for lymph node metastases in prostate adenocarcinoma. There is no consensus on the optimal sampling method of PLND specimens among pathologists. This study analyzed the effectiveness of the submission of entire adipose tissue in 451 cases and its impact on total lymph node yield and detection of positive lymph nodes. The sizes of metastatic foci and positive lymph nodes in 83 cases were also studied. Submission of entire adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Adipose tissue in pelvic lymph node dissection specimens was submitted in toto for histologic analysis after dissection of grossly visible lymph nodes. 13 As our study included patients over a time period when International Society of Urological Pathology (ISUP) conducted 2 modifications of PCa grading, 1416 we re-reviewed biopsies for cases that were upgraded at RP and identified 1 case from 2004 that had occasional small cribriform glands graded as pattern 4 in current practice (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Adipose tissue in pelvic lymph node dissection specimens was submitted in toto for histologic analysis after dissection of grossly visible lymph nodes. 13 As our study included patients over a time period when International Society of Urological Pathology (ISUP) conducted 2 modifications of PCa grading, 1416 we re-reviewed biopsies for cases that were upgraded at RP and identified 1 case from 2004 that had occasional small cribriform glands graded as pattern 4 in current practice (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Not surprisingly, studies have shown that total embedding can increase the nodal yield following RP and RC and may improve the detection of metastases, particularly in PCa, where there is a poor correlation between LN size and metastatic involvement . Yoon et al . and Perry‐Keene et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a previous survey on PCa conducted by the International Society of Urological Pathology (ISUP), 27% of members submitted the entire PLND specimen . Not surprisingly, studies have shown that total embedding can increase the nodal yield following RP and RC and may improve the detection of metastases, particularly in PCa, where there is a poor correlation between LN size and metastatic involvement . Yoon et al .…”
Section: Discussionmentioning
confidence: 99%
“…An increase in metastatic lymph node detection and increased N-stage would warrant a change in clinical management, potentially with implementation of adjuvant therapies. Specifically, Yoon et al 13 introduced the benefit of submitting all lymph node packet adipose tissue, specifically in detecting metastatic deposits of prostate cancer. It will be important to evaluate the potential value of improved staging and prognostication provided by implementation of this new grossing technique in the setting of the increased cost incurred for paraffin blocks, slides, pathologist evaluation, reporting, and storage.…”
Section: Discussionmentioning
confidence: 99%
“…From the surgical pathology perspective, improved techniques of tissue processing have been proposed and implemented to provide a higher nodal count for evaluation based on the tissue packets removed at time of surgery. [11][12][13] In an attempt to increase the identification of lymph nodes detected in pelvic lymphadenectomy specimens, we implemented a new tissue processing protocol at our institution's surgical pathology department. We demonstrate the difference in lymph node yield in both RP and RC cases before and after implementation of this protocol at our institution, with no significant alteration in surgical lymphadenectomy template at the time of surgery.…”
Section: Introductionmentioning
confidence: 99%